Textbook on additives and addictive substances with a scientific-based approach, a research and development - Siska Elis Mahmudah; Iin Hindun; Roimil Latifa; H. Husamah; Dwi Setyawan (Universitas Muhammadiyah Malang, 2021)
Improving learning activities requires teaching materials that can accommodate students' scientific skills. This study aims to produce textbooks for additives and addictive substances with a scientific approach and analyze their validity and effectiveness. This research and development used the Borg & Gall model which consists of 10 steps. Products are validated by media experts and material experts. The product trial used a limited test with 15 students of seventh grade in junior high school. The validation results show that the product is valid and very good. Meanwhile, the results of the trial of student responses to the use of the average value of 89.13% and learning outcomes increased by 87%. Thus, the textbooks developed are very suitable for use in the learning process.